INFLUENCE OF SALINITY ON GERMINATION, SEEDLING GROWTH, ION CONTENT AND ACID PHOSPHATASE ACTIVITIES OF Linum usitatissimumL. - N. Nasri 1—; S. Maatallah2—; I. Saidi; M. Lachaâl (Journal of Animal and Plant Sciences, 2017)
The aim of this work was to investigate the effect of different concentrations of NaCl (0 mM, 100 mM, 200 mM and 300 mM) on germination, seedling growth and acid phosphatase activity of Linum usitatissimum seeds. Flax seeds were germinated under control and saline (100, 200 and 300 mM NaCl) conditions and the effect of salt stress on germination and enzyme activity was determined. Final germination percentage was reduced at higher concentrations than 100 mM and was annulated at the highest salt concentration (300 mM NaCl). However, seedling growth was inhibited by all salt concentrations. The Na content of seeds after imbibitions significantly increased with increasing salinity but K+ content decreased. The effect of saline treatment on hydrolytic enzymes activities varied, depending on the concentration of NaCl and the organ of seedlings. However, radicle acid phosphatase activity exhibited a decrease in flax seedlings after 48h and 96h of germination under 100 and 200 mM NaCl. In hypocotyl and cotyledons, this activity showed no difference compared with the control under salt stress after 48h and 96h of growth.
Keywords: Germination; seedling growth; salinity; acid phosphatase activity; Linum usitatissimum